Long-term predictability of allogenic dermal matrix for root coverage: Three years observation period on 15 consecutive cases - Khalid Al-Hamdan (Elsevier, 2021)
Gingival recession is an apical migration of gingival margin that is a common finding on patients with meticulous oral hygiene and periodontitis patients. Several surgical treatment techniques of gingival recession have been described. The most challenging situation is the presence of multiple adjacent recession defects. 15 patients with total of 53 recession defects have been treated with Acellular Dermal Matrix (ADM). The following clinical parameters were evaluated recession depth (RD), probing depth (PD); and the width of the keratinized tissue (KT). Upon completion of the study; there was statistically significant (P-value = 0.00) reduction in recession depth from baseline, one and three years after the surgery (2.6 mm, 0.32 mm, and 0.17 mm, respectively). There was statistically significant (P-value = 0.00) increase in the width of keratinized tissue from baseline to one year and three years (3.47 mm, 5.02 mm, and 5.40 mm, respectively). Based on this study the use of ADM with the coronally advanced flap resulted in a significant increase in keratinized tissue and percentage of root surface coverage.